If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(7X + Y) = -6 (7X * 4 + Y * 4) = -6 (28X + 4Y) = -6 Solving 28X + 4Y = -6 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4Y' to each side of the equation. 28X + 4Y + -4Y = -6 + -4Y Combine like terms: 4Y + -4Y = 0 28X + 0 = -6 + -4Y 28X = -6 + -4Y Divide each side by '28'. X = -0.2142857143 + -0.1428571429Y Simplifying X = -0.2142857143 + -0.1428571429Y
| 5[x+1]+6=21 | | 5t-4=2t+6 | | 123456789i^2=987654321 | | 123456789i^2=76 | | 5a+3b=16 | | 3x+4.5(8)=4(x+8) | | 3(x+5)-3=2 | | Pi^2=76 | | (x-50)(x-20)=0 | | x^2-70x+1000=0 | | 5a-a+3a= | | 9w-16=5.3 | | 2x-x=11 | | 4(x^2-70x+1000)=0 | | 10(4x-8)=100x | | 4x^2-280x+4000=0 | | 4x-1=6x+4 | | 4x^2-280x+4800=800 | | 8.04x+36=64.6416+6x | | 8.04+36=64.6416+6x | | 4800-120x-160x+4x^2=800 | | -4-6x=-8x | | 168-2x=25x+18 | | [5x]=70 | | 2x-60=-6x+20 | | x^4-15x^2+25=0 | | (60-2x)(80-2x)=800 | | 12x^3-x^2-20x=0 | | 8n^2+10n+5=0 | | 3x^2=6-5 | | v=ir | | C(m)=0.15m+0.75 |